Pricing Climate Risks: Evidence from Wildfires and Municipal Bonds - Woongchan Jeon; Lint Barrage; Kieran James Walsh (CESifo GmbH, 2024)
How are financial markets responding to anticipated climate-driven wildfire risk increases? Combining high-resolution meteorological predictions and land use pattern maps with detailed US municipal bond data, this paper finds that municipalities facing higher future wildfire risk increases are already having to pay substantially higher borrowing costs as a result. A one standard deviation increase in future wildfire exposure is associated with a 23-basis point rise in school district bond spreads, corresponding to 42% of the sample mean. Borrowing cost impacts are significantly larger in areas with higher minority population shares and heavier reliance on local revenue sources.
Keywords: G12; H74; Q54; 330; wildfires; climate risk; municipal bond; fiscal costs of climate change